Effect of ripe plantain peel (Musa cv) on growth and carcass performance of growing rabbits - Amos Oladipo, Fanimo; Odu, Sunday (Universiti Putra Malaysia Press, 1996)
A feeding trial was conducted using 48 New Zealand White x Flemish Giant weaner rabbits to determine the replacement value of ripe plantain peel for maize in weaner rabbit diets. Ripe plantain peel was used to replace maize at 0,33, 66 and 100% in a practical weaner diet. Average daily gain and feed/gain were depressed (P < 0.05) at the 100% replacement level. Dry matter, crude protein and energy digestibility coefficient were significantly (P < 0.05) depressed by inclusion of ripe plantain peel in the diet. However, the inclusion of ripe plantain peel had no significant effect on average feed intake and crude fibre digestibility. Dressing percentage, lumbar region weight and breast weight were also depressed (P < 0.05) by the 100% replacement level of ripe plantain peel, while inclusion of ripe plantain peel in the diet increased (P < 0.05) the viscera weight.